2009
DOI: 10.1080/01904160802715620
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phosphorus Application on Clusterbean under Different Intensities of Water Stress

Abstract: Response of clusterbean [Cyamopsis tetragonoloba (L.) Taub.] to phosphorus (P) application (0 and 40 kg ha −1 ) under different intensities of water stress at the critical pre-flowering stage was studied in a pot trial by withholding irrigation for 0, 3, 6, and 9 days. Increasing stress intensity progressively decreased plant water potential ( plant ), relative water content, levels of different leaf metabolites, photosynthetic rate, and nitrate reductase activity under both phosphorus (P) treatments. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
24
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 30 publications
8
24
1
Order By: Relevance
“…In our study, P application, to a certain extent, increased starch content of water-stressed dwarf bamboo (Table 3), possibly due to higher P n and/or an obvious decline in AMY activity. Similar findings have been described previously in Vigna aconitifolia and Cyamopsis tetragonoloba (Burman et al, 2009). Therefore, P application could tightly regulate starch synthesis and degradation under water stress to avoid periods of starvation.…”
supporting
confidence: 74%
See 4 more Smart Citations
“…In our study, P application, to a certain extent, increased starch content of water-stressed dwarf bamboo (Table 3), possibly due to higher P n and/or an obvious decline in AMY activity. Similar findings have been described previously in Vigna aconitifolia and Cyamopsis tetragonoloba (Burman et al, 2009). Therefore, P application could tightly regulate starch synthesis and degradation under water stress to avoid periods of starvation.…”
supporting
confidence: 74%
“…Several studies have shown that P fertilization can directly enhance LRWC, as well as free and bound water components in water-stressed plants (Singh et al, 2006a;Sato et al, 2010). However, P application had minimal effect on LRWC of dwarf bamboo, regardless of water availability (Table 2), as also shown in previous studies of other crop species Singh et al, 2006b;Burman et al, 2009). Moreover, the LRWC of dwarf bamboo was influenced by water-P interaction (Table 6), which is due to interactive effects on leaf area Garg et al, 2004).…”
Section: Growth and Water Statussupporting
confidence: 61%
See 3 more Smart Citations